In vitro effects of endodontic irrigants on endotoxins in root canals - de Oliveira, Luciane Dias; Cardoso Jorge, Antonio Olavo; Talge Carvalho, Cludio Antonio; Koga-Ito, Cristiane Yumi; Valera, Marcia Carneiro (Elsevier B.V., 2007)
Objective. The objective of this study was to evaluate the effects of endodontic irrigants on endotoxins in root canals.Study design. Ninety-eight single-root human teeth were used. Escherichia coli endotoxin was inoculated into 84 root canals. All root canals were enlarged and assigned to 7 groups (n = 14), according to solution used. Group 1 (G1): 2.5% NaOCl; G2: 5.25% NaOCl; G3: 2% chlorhexidine; G4: 0.14% calcium hydroxide; G5: polymyxin B; G6: positive control, saline solution; G7: negative control (no endotoxin). Two samplings of root canal were accomplished: immediate and after 7 days. Detoxification of endotoxin was evaluated by Limulus assay and antibody production in B-lymphocyte culture. Results were analyzed by Kruskal-Wallis/Dunn and ANOVA/Tukey.Results. At the immediate and second samplings, groups G4, G5, and G7 presented the best results, significantly different from groups G1, G2, G3, and G6 (P = .05).Conclusions. Calcium hydroxide and polymyxin B detoxified endotoxin in root canals and altered properties of LPS to stimulate the antibody production by B-lymphocytes. Sodium hypochlorite and chlorhexidine did not detoxify endotoxin.